2016
DOI: 10.1016/j.jtos.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Niche Regulation of Limbal Epithelial Stem Cells: Relationship between Inflammation and Regeneration

Abstract: Human limbal palisades of Vogt are the ideal site for studying and practicing regenerative medicine due to their accessibility. Nonresolving inflammation in limbal stroma is common manifestation of limbal stem cell (SC) deficiency and presents as a threat to the success of transplanted limbal epithelial SCs. This pathologic process can be overcome by transplantation of cryopreserved human amniotic membrane (AM), which exerts anti-inflammatory, antiscarring and anti-angiogenic action to promote wound healing. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 143 publications
(178 reference statements)
1
49
0
1
Order By: Relevance
“…The therapeutic benefit observed herein in reducing inflammation and scarring as well as to promote epithelial wound healing is consistent with what has been summarized recently (reviewed in 22 and 23 ). In addition to the non-specific antiviral immunity yielded by the endogenous interferon in human placenta, 24,25 recent study identified the board anti-inflammatory action in CAM applies to activated but not resting neutrophils, 26,27 macrophages, 27 and lymphocytes 26 extending from innate to adaptive immune responses.…”
Section: Discussionsupporting
confidence: 91%
“…The therapeutic benefit observed herein in reducing inflammation and scarring as well as to promote epithelial wound healing is consistent with what has been summarized recently (reviewed in 22 and 23 ). In addition to the non-specific antiviral immunity yielded by the endogenous interferon in human placenta, 24,25 recent study identified the board anti-inflammatory action in CAM applies to activated but not resting neutrophils, 26,27 macrophages, 27 and lymphocytes 26 extending from innate to adaptive immune responses.…”
Section: Discussionsupporting
confidence: 91%
“…Typically, in lens epithelial cultures, cell division ceases after 5–7 population doublings (Jacob, 1987). Second, the lens epithelium lacks an obvious stem cell niche analogous, for example, to the palisades of Vogt of the corneal limbus, which are believed to harbor the corneal stem cell population (Tseng et al, 2016). Third, lineage tracing experiments in the lens have failed to identify putative stem cells.…”
Section: Anatomy Of the Growth Processmentioning
confidence: 99%
“…Creation of a whole limbal niche is under investigation by tissue engineering approaches [22]. Applying anti-inflammatory tissues like amniotic membrane and its derivatives [9•], blood-derived products [57], and growth factors [58] have revealed significant results in experimental studies. One novel method which has shown promising results is the application of mesenchymal stem cells (MSCs) and/or their trophic factors [32•].…”
Section: Therapeutic Approaches: Restoring the Limbal Niche As A Prommentioning
confidence: 99%
“…One of the important recent concepts is that of the “limbal niche”, a specialized microenvironment in the limbus which regulates the LESC function [68]. The pivotal role of the limbal niche for maintaining the “stemness” of LESCs and the effect of disturbance of the limbal niche on corneal epithelial homeostasis have been addressed in several studies [9•]. In this review, the current opinions of the authors on the mechanisms of corneal epithelial homeostasis are reviewed and the characteristics of the limbal niche is presented.…”
Section: Introductionmentioning
confidence: 99%